PENGARUH NILAI BUDAYA DAN UNSUR AUTENTIK LUDRUK PADA MINDSET MASYARAKAT TERHADAP HEGEMONI WARIA DI INDONESIA - Eko Heriyanto (Universitas Aki, 2017)
Through the massive effort of transvestites to be accepted by the community, it seems that people are beginning to accept the presence of them. This raises a new phenomenon in the life of Indonesian society. It is a shift in cultural values and conflicts that further sharpen and complicate the situation in Indonesia. It is caused by the low mindset of the people to accept the balance of information between pros and cons against transvestites.The objectives of the research are to: know the current development ofLudruk performance and the condition of active and passive Ludruk players; know the public opinion about the current condition of the transvestites which are increasingly advanced in various sectors of life and overcome to be a transvestite in the next future; provide an overview of Ludruk as one of the traditional performance that are able to fight (subvert) the hegemony of transvestites that occur in society these days; build public opinion to always support the preservation of Ludruk as valuable Indonesian cultural heritage.This research method is descriptive qualitative. Primary data is documentation of Ludruk. Secondary data are questionnaire and interview by using sampling method. Data analysis technique that we use is recapitulate 100 respondent opinion as sample research.The results of this study are: (1) there are many people who know Ludruk. Ludruk worsened, because marginalized by television shows, (2) respondents argue that being transvestite now offers a lot of success, (3) Ludruk is able to give new overview for the community against transvestites, (4) respondents welcomed well and support when Ludruk can be performed on television.Key words: transvestite, subversion, hegemony, Ludruk performance.